Decision making power over reproductive health service utilization among married Ethiopian women: cross sectional study - Dessalegn Nigatu Rundasa; Zerihun Bayabil; Tarekegn Fekede (International Journal of Public Health Science (IJPHS), 2022)
Decision-making power of women is one of the essential factors which influence maternal health service utilization. Women's lack of decision over reproductive health service utilization affects their protection from unwanted childbearing, unsafe sex, and their consequences. To assess decision-making power on Reproductive Health service utilization and its associated factors among married women in South West Ethiopia, 2020. Cross-sectional study was conducted from May to July 2020 among 584 married women of the reproductive age. A total of 288 in urban and 288 in rural married women were interviewed and these yields a response rate of 98.6% both in urban and rural. Decision-making power over reproductive health service utilization in urban and rural was 55.2% [95% CI (52.7-64.6)] and 40.3% [95% CI (39.9-52.5)] respectively. In urban, being wives of government-employed spouses [AOR 2.102 95% CI (1.16, 3.81)], knowledge on RH [AOR 3.33, 95% CI (1.20, 12.49)], above five years in marriage [AOR 1.91, 95% CI (1.19,7.70)], were found to be predictors of women’s decision-making power over reproductive health use. The study revealed that in urban settings those women who had marriage duration five and more than five years, being wives of government-employed spouses had more likely decision-making power on reproductive health utilization but not in rural settings. Hence, reproductive health interventions in the area should be promoted by considering empowering married women on reproductive health service utilization.